2017
DOI: 10.5897/ajb2017.16247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adenine sulphate, casein hydrolysate and spermidine on in vitro shoot multiplication of two banana varieties (FHIA-21 and PITA-3)

Abstract: A highly reproducible and efficient in vitro shoot regeneration system was developed for two banana varieties (FHIA-21 and PITA-3) using shoot tip as explant. Shoot tip was inoculated onto Murashige and Skoog (MS, 1962) medium supplemented with cytokinins [benzylaminopurine (BAP), kinetin (Kin) and 2-isopentenyl (2-iP)] and additives [Adenine sulphate (Ads), spermidine (Spd) and casein hydrolysate (CH)] for shoot multiplication. In all varieties, the maximum number of shoots and shoot length was obtained with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Previous studies revealed the positive impact of growth additives in the regeneration frequency of several plant species. For instance, the use of 25 to 50 mg/l of casein hydrolysate in combination with 4 mg/l BAP significantly improved shoot regeneration in bananas [16]. Similarly, the addition of 500 mg/l casein hydrolysate into the MS medium having 1 μM BAP induced the maximum shoot number in Neem tree [17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed the positive impact of growth additives in the regeneration frequency of several plant species. For instance, the use of 25 to 50 mg/l of casein hydrolysate in combination with 4 mg/l BAP significantly improved shoot regeneration in bananas [16]. Similarly, the addition of 500 mg/l casein hydrolysate into the MS medium having 1 μM BAP induced the maximum shoot number in Neem tree [17].…”
Section: Introductionmentioning
confidence: 99%